2012
DOI: 10.1111/j.1365-2966.2012.20586.x
|View full text |Cite
|
Sign up to set email alerts
|

Substructure in the most massive GEEC groups: field-like populations in dynamically active groups

Abstract: The presence of substructure in galaxy groups and clusters is believed to be a sign of recent galaxy accretion and can be used to probe not only the assembly history of these structures, but also the evolution of their member galaxies. Using the Dressler–Shectman (DS) test, we study substructure in a sample of intermediate‐redshift (z∼ 0.4) galaxy groups from the Group Environment and Evolution Collaboration (GEEC) group catalogue. We find that four of the 15 rich GEEC groups, with an average velocity dispersi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
89
1

Year Published

2012
2012
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 57 publications
(96 citation statements)
references
References 69 publications
(143 reference statements)
6
89
1
Order By: Relevance
“…Therefore, for simplicity, in our analysis, we only use EW classification to detect SF, but separating galaxies by sSFR produces essentially identical conclusions. As a check on our SF analysis, and to more readily compare our conclusions with past studies (e.g., Tomita et al 1996;Metevier et al 2000;Hou et al 2012), we also investigate the presence of blue galaxies in our clusters. As described in Hwang & Lee (2009), blue and red galaxies are separated by a line in 0.1 (u−r)-M 0.1 r space defined by Choi et al (2007) and fit by eye here.…”
Section: Datamentioning
confidence: 90%
See 1 more Smart Citation
“…Therefore, for simplicity, in our analysis, we only use EW classification to detect SF, but separating galaxies by sSFR produces essentially identical conclusions. As a check on our SF analysis, and to more readily compare our conclusions with past studies (e.g., Tomita et al 1996;Metevier et al 2000;Hou et al 2012), we also investigate the presence of blue galaxies in our clusters. As described in Hwang & Lee (2009), blue and red galaxies are separated by a line in 0.1 (u−r)-M 0.1 r space defined by Choi et al (2007) and fit by eye here.…”
Section: Datamentioning
confidence: 90%
“…Several clusters show an enhanced presence of emission-line galaxies in clusters with substructure: for example, A1367 (Cortese et al 2004), A3158 (Johnston-Hollitt et al 2008), the "bullet cluster" (Rawle et al 2010), and A2465 (Wegner 2011). In the Group Environment and Evolution Collaboration group catalog, Hou et al (2012) found higher fractions of blue and star-forming galaxies in rich groups with substructure than in those without, but Hou et al (2013) found no correlation between quiescent fraction and group dynamical state. Similarly, Metevier et al (2000) found high blue galaxy fractions in A98 and A115 that they attributed to the merging of subclusters, but they found no such correlation in A2356.…”
Section: Introductionmentioning
confidence: 96%
“…Therefore, systems with significant substructures show low-P DS values. The Monte Carlo realization of the Δ DS statistic yields P DS = 0.06 for R1504, which only corresponds to a ∼10% false detection according to Hou et al (2012). This P DS -value thus represents a non-negligible possibility that the high velocity group exists.…”
Section: Two-dimensional Kinematic Structurementioning
confidence: 99%
“…The probability of having substructures can be estimated by P DS = n MC j=1 δ j /n MC , in which δ j = Δ DS,j when Δ DS,j > Δ DS,obs and δ j = 0 otherwise (e.g. Hou et al 2012). Therefore, systems with significant substructures show low-P DS values.…”
Section: Two-dimensional Kinematic Structurementioning
confidence: 99%
“…5, the scatter is present in both directions, confirming this assertion. On the other hand, even if some galaxy groups look like simple lensing objects (but see Orban de Xivry & Marshall 2009;Limousin et al 2010), they could be dynamical complex objects with multimodal components and substructures (e.g., Hou et al 2009Hou et al , 2012Ribeiro et al 2013). Some of our groups have luminous morphologies (Foëx et al 2013) that cannot be associated with regular groups (roughly circular isophotes around the strong lensing system) and have elongated (elliptical isophotes with a roughly constant position angle form inner to outer parts) or multimodal morphologies (two or more peaks in the central part of the map).…”
Section: R a Vs θ Ementioning
confidence: 99%